Health visiting teams and children's oral health: a scoping review - Sarab El-Yousfi; Zoe Marshman; Patricia N. Albers; Samantha Watt; Ruth Kipping; Joanna G. Williams (BMC, 2022)
Abstract Background Recent policies have recommended early-life interventions to prevent caries. The four nations of the UK each have a national universal children's health programme, through which health visitors and their wider team (HVTs) promote health in the early years. HVT visits offer an opportunity to support parents to improve their child's oral health. A scoping review was conducted to provide a descriptive synthesis of the current literature related to the role of HVTs in improving the oral health of children 0-5 years old and to identify significant gaps for future research. This review informed the feasibility study of the First Dental Steps Intervention, a targeted health visitor-led infant oral health intervention in England. Methods Electronic database searches for peer-reviewed literature were performed using Medline via Ovid and Web of Science (1946-2021). The quality of included intervention studies was assessed using the Effective Public Health Practice Project tool. Additionally, a grey literature search was conducted (key organisations, bibliographic and thesis databases, forwards and backwards citation, Google). Results Thirty-nine publications, published between 1980 and 2021, were included. The majority of included papers were from the UK. The quality of intervention studies (n = 7) ranged from weak to strong. Thematic analysis identified the following themes: (1) professional knowledge, education, and training; (2) involvement of HVs in the delivery of oral health interventions; (3) effectiveness of interventions; (4) perspectives of HVs providing oral health advice and acceptability; and (5) barriers and facilitators to promoting oral health. The grey literature search identified 125 sources. HVT involvement was reported in a variety of source types: reports, guidance documents, evaluations, reviews, and training resources. HVTs were involved in oral health by providing oral health packs, brushing and oral health advice, registration and attendance, oral health training, risk assessment, and referral to dental services. Conclusion The current literature suggests that HVTs are well placed to improve children's oral health. Facilitators and barriers are encountered by HVTs in promoting oral health which should be considered by commissioners. There is a need for future high-quality studies that address the inadequacies found and provide further evidence of the effectiveness of HVT's oral health interventions.